A STUDY OF THE SILYLATION REACTION OF IMINES WITH TRIMETHYLCHLOROSILANE IN THE PRESENCE OF LITHIUM (Journal of Sciences, Islamic Republic of Iran)
A mixture oftrimethylchlorosilane (TMS-Cl), lithium and tetrahydrofuran (THF) reacts with imines to produce disilyl compound by addition of two trimethylsilyl (TMS) groups to the double bond of the imine. On hydrolysis the TMS on nitrogen is substituted by hydrogen and yields ? -silylamine. In the presence of acetyl chloride (CH COC1), benzene and pyridine, the ?-silyamine produces the corresponding amides.Finally, the related tertiary silylamines have been prepared.